Analysing secondary infections of Coronavirus Disease 2019 across the Geopolitical zones of Nigeria using estimated time dependent reproduction number - Muhammed Umar Bibi; Saad Ahmed Aliyu; Idris M Jega (Sriwijaya Journal of Environment, 2020)
Time dependent reproduction number (TD – R0) is a measure of secondary infections or transmissibility of a disease useful in monitoring changes in the rate of infection and assessing policies put in place to control the spread of a disease. In this study we used daily infections situation report of COVID – 19 published by the Nigeria Centre for Disease Control (NCDC) to estimate Nigeria’s TD – R0 and then repeated the same for the six geo – political zones in the country. Estimates of TD – R0 values for the country from the 23rd of March – 27th of May 2020 fluctuated with a maximum of 2.3 (95% CrI) on the 19th of April and a minimum of 0.83 (95% CrI) on the 16th May 2020. Despite the decline in TD – R0 since the early stages of the outbreak of COVID – 19 in Nigeria suggesting a fall in the expected rate of secondary infection apart from the northwest and the northeast geo – political zones values remain above 1.0 for other zones and the country, generally. The Kolmogorov – Smirnov (KS) test was used to test the null hypothesis stating that the means of TD – R0 across the geo-political zones does not follow the same distribution pattern. After making adjustments for Type 1 – error we accepted the null hypothesis (p < 0.05) for six pairs of geo-political zones. We conclude that our findings are significant in studying the COVID – 19 epidemic in Nigeria and important in evaluating the strategies deployed by governments at the national and regional levels, thus, the same method can be replicated across Africa.